Analisis Hermeneutika Pengorbanan Generasi Sandwich dalam Film 1 Kakak 7 Ponakan - Wita Amelia Makkiyah; Nawiroh Vera; Sinta Dwi Utami (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
The sandwich generation phenomenon has become a relevant issue in society, where individuals must shoulder family responsibilities while also meeting their personal needs. The film 1 Kakak 7 Ponakan depicts this situation through the character Moko, who must care for his nieces and nephews. This study aims to analyze the representation of the sandwich generation’s sacrifices in the film. This study employs a qualitative method using Friedrich Schleiermacher’s hermeneutic approach through grammatical and psychological interpretation, with the analysis focusing on scenes and dialogues that represent the sacrifices of the sandwich generation, as well as conditions illustrating the conflict between personal interests and family responsibilities experienced by the character Moko. Data collection techniques involved observing scenes and dialogues in the film, supported by relevant literature reviews. The results of the study indicate that the character Moko experiences a role conflict between personal interests and family responsibilities. The sacrifices Moko makes are not limited to financial considerations, they also encompass emotional and long-term aspects, such as postponing education, losing a job, and sacrificing personal relationships. The film’s findings not only highlight individual conflicts but also reflect the social reality of balancing personal life with family responsibilities. Thes The sacrifices Moko makes are not limited to financial considerations; they also encompass emotional and long-term aspects, such as postponing education, losing a job, and sacrificing personal relationships. The film’s findings not only highlight individual conflicts but also reflect the e circumstances demonstrate that sacrifice is an integral part of that role.